Interpretation of Qur'anic Verses in the Procession of Tari Topeng: Perspective of Desa Slangit Community, Cirebon - Fitria, Fitria; Maimun, Muhammad; Ramdhani, Suciyadi; Qosim, Ida Nor (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2025)
Purpose-This study aims to explore the symbolic meanings of Qur'anic verses in Tari Topeng tradition that has developed in Slangit Village, Cirebon. In this village, Tari Topeng is not merely a performance of art, but also a medium for conveying profound spiritual messages, heavily influenced by Islamic teachings. Design/methods/approach- Using a qualitative approach, this research identifies various symbols and meanings embedded in each stage of the procession, as well as the mask characters used during the performance. Findings- The study reveals how the Tari Topeng dancers in Slangit Village interpret Qur'anic verses within their artistic tradition. Prior to the performance, the recitation of Qur'anic verses is performed through four main stages: first, Dalang (puppet master) undergoes a spiritual cleansing ritual; second, the dalang recites prayers, wirid, and Qur'anic surahs for the safety of the performance; third, the dalang conducts a duduk manji to seek permission from the ancestors; and fourth, the masks are maintained every Friday night with prayers and salawat. Additionally, the mask characters used in the performance carry meanings that reflect the content of the Qur'anic verses. Research Implications- This research highlights that traditional arts, such as Tari Topeng, possess a strong religious dimension that shapes both the cultural and spiritual identity of Desa Slangit community.